Self-cleaning UV coating and preparation method thereof

By wrapping zinc oxide in organic polymer and preparing antibacterial particles, the problem of nano-scale ZnO particles easily aggregation in the paint is solved, significantly improving the antibacterial and mechanical properties of the paint, and achieving self-cleaning function.

CN119081536BActive Publication Date: 2025-02-14SHAOGUAN HEZHONG CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411343244.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-14
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Nano-scale ZnO particles are prone to aggregation in the coating, resulting in poor dispersion and compatibility, and their antibacterial and special properties cannot be fully utilized.

Method used

By encapsulating zinc oxide in organic polymers, antibacterial particles are formed and the dispersion and compatibility of the particles are improved through specific process steps, enhancing their stability and performance in the coating.

Benefits of technology

It significantly improves the antibacterial and mechanical properties of the coating, realizes the self-cleaning function of the coating, and enhances its resistance to dust and dirt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005060289580000121
    Figure BDA0005060289580000121
  • Figure BDA0005060289580000131
    Figure BDA0005060289580000131
Patent Text Reader

Abstract

The present invention relates to a self-cleaning UV coating and a preparation method thereof, and belongs to the technical field of UV coatings. A self-cleaning UV coating comprises the following components: an aqueous polyurethane acrylate emulsion, a reactive monomer, antibacterial particles, a photoinitiator, a defoaming agent, a dispersant, a leveling agent, white carbon black, a cosolvent and deionized water. The antibacterial particles prepared by the present invention are composed of zinc oxide wrapped in an organic polymer, which improves the dispersibility and compatibility of zinc oxide in the coating system. The wrapped zinc oxide contains a variety of groups and can be used as a compatibilizer at the interface between white carbon black and the coating system, thereby improving the antibacterial and mechanical properties of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of UV coatings and relates to a self-cleaning UV coating and a preparation method thereof. Background Art

[0002] Ultraviolet light-curing coatings (UV coatings) are a new type of coating that emerged in Europe, America, Japan and other regions in the late 20th century. Because the cured coating exhibits excellent scratch resistance, high hardness and good fullness, and has multiple advantages such as high efficiency, energy saving, environmental protection and economy, the coating has been widely used in many fields such as construction, sporting goods, electronic communications, packaging materials and automotive parts. In particular, UV-curing coatings with self-cleaning functions, by giving the substrate unique physical and chemical properties, enable the substrate to achieve self-cleaning without the need for traditional manual cleaning methods, and have become an innovative product that has received increasing attention in the field of UV coatings in recent years.

[0003] ZnO is a multifunctional and promising inorganic material belonging to the II-VI semiconductor. It has piezoelectric, semiconductor, chemical sensing, conductivity and optical properties. Its characteristics include direct wide bandgap (3.3eV) in the near-ultraviolet spectrum, high exciton binding energy (60meV) and natural n-type conductivity, and it is widely used in many fields. In addition, zinc oxide also exhibits significant antibacterial properties and is relatively inexpensive. ZnO materials modified by nanotechnology also show a variety of special properties caused by the size effect of nanoparticles. Nanoscale ZnO particles can effectively eliminate a variety of bacteria and microorganisms, including Escherichia coli, Staphylococcus aureus, Gram-negative bacteria, etc. due to their large total surface area and enhanced ability to penetrate biofilms. However, one of the main challenges currently faced in the application field of nanoparticles is the aggregation problem of nanoparticles. Nanoscale ZnO particles have a large specific surface area due to their size at the nanoscale, resulting in a wide contact surface between particles, and are easy to aggregate to form larger particles, thus failing to give full play to the special properties of nanomaterials. The aggregation phenomenon is particularly significant when nanoparticles are mixed with polymer materials or applied in coatings. Summary of the invention

[0004] The purpose of the present invention is to provide a self-cleaning UV coating and a preparation method thereof. The antibacterial particles prepared by the present invention are composed of zinc oxide wrapped by an organic polymer, which improves the dispersibility and compatibility of zinc oxide in the coating system. The wrapped zinc oxide contains multiple groups and can be used as a compatibilizer at the interface between white carbon black and the coating system, thereby improving the antibacterial and mechanical properties of the coating.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A self-cleaning UV coating comprises the following components by weight: 52-68 parts of waterborne polyurethane acrylate emulsion, 5-8 parts of reactive monomers, 10-13 parts of antibacterial particles, 2-3 parts of photoinitiators, 0.2-0.4 parts of defoamers, 0.2-0.3 parts of dispersants, 1-2 parts of leveling agents, 4-6 parts of white carbon black, 2-4 parts of cosolvents and 24-30 parts of deionized water.

[0007] As a preferred technical solution of the present invention, the reaction monomer is prepared by mixing methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3-4:2-5; the waterborne polyurethane acrylate emulsion is selected from DR-W485 of Changxing Chemical.

[0008] As a preferred technical solution of the present invention, the photoinitiator is photoinitiator 184, namely 1-hydroxycyclohexyl phenyl ketone.

[0009] As a preferred technical solution of the present invention, the defoaming agent is one or more of BYK019, BYK-020 and BYK-1794.

[0010] As a preferred technical solution of the present invention, the dispersant is BYK190.

[0011] As a preferred technical solution of the present invention, the leveling agent is a polyether siloxane copolymer leveling agent, preferably BYK-3455.

[0012] As a preferred technical solution of the present invention, the co-solvent is one or two of ethylene glycol butyl ether, propylene glycol butyl ether and propylene glycol methyl ether.

[0013] The preparation of the antibacterial particles comprises the following steps:

[0014] 1) placing zinc oxide in an ethanol solution and mixing it by ultrasonication, adding a silane coupling agent, heating and stirring the mixture, cooling to room temperature, centrifuging and washing the solid, placing it in an oven and vacuum drying it to obtain prefabricated particles;

[0015] 2) in an inert atmosphere, mechanically stirring and mixing the prefabricated particles and the organic solvent, adding eugenol, oleic acid and glycidyl methacrylate and stirring at high speed, adding an initiator and heating and stirring, cooling to room temperature, centrifuging, washing, placing in an oven and vacuum drying to obtain a modified composite;

[0016] 3) The modified complex is immersed in a perillaldehyde solution and stirred at elevated temperature for purification, and then placed in an oven for vacuum drying to obtain antibacterial particles.

[0017] As a preferred technical solution of the present invention, in step 1), the ultrasonic mixing is performed at a frequency of 200-300W for 20-30min; the heating stirring and mixing is performed at a temperature of 50-60°C for 3-4h.

[0018] As a preferred technical solution of the present invention, in step 1), the washing is washing with anhydrous ethanol three times; and the vacuum drying is vacuum drying at a temperature of 80-90° C. for 6-8 hours.

[0019] As a preferred technical solution of the present invention, in step 1), the mass ratio of the zinc oxide, ethanol solution and silane coupling agent is 20-26:60-70:8-10; the silane coupling agent is silane coupling agent NQ62; in the embodiments of the present invention and the comparative examples, the mass fraction of the ethanol solution is 95%.

[0020] As a preferred technical solution of the present invention, in step 2), the inert atmosphere is a nitrogen inert atmosphere; the mechanical stirring and mixing is stirring and mixing at a speed of 500-800 r / min for 15-20 min; the high-speed stirring is high-speed stirring at a speed of 1000-1200 r / min for 30-40 min; the heating stirring is stirring at a temperature of 60-70°C for 5-6 h.

[0021] As a preferred technical solution of the present invention, in step 2), the washing is washing with anhydrous ethanol three times; and the vacuum drying is vacuum drying at a temperature of 70-80° C. for 8-10 hours.

[0022] As a preferred technical solution of the present invention, in step 2), the mass ratio of the prefabricated particles, the organic solvent, eugenol, oleic acid, glycidyl methacrylate and the initiator is 20-30:60-70:11-12:2.2-2.6:16-18:0.8-1.0.

[0023] As a preferred technical solution of the present invention, firstly, oleic acid has certain antibacterial activity. Oleic acid is a fatty acid with strong lipophilicity, which can interact with lipids in bacterial cell membranes, destroy the integrity of bacterial cell membranes, increase the permeability of bacterial cells, and eventually lead to bacterial death; in addition, oleic acid can also interfere with the metabolic process of bacteria, affect the normal growth and reproduction of bacteria, and thus play an antibacterial role.

[0024] As a preferred technical solution of the present invention, nano-sized zinc oxide penetrates bacterial cell membranes and ZnO nanoparticles promote the generation of active oxygen free radicals, which can kill bacteria and thus achieve an antibacterial effect.

[0025] As a preferred technical solution of the present invention, in step 2), the organic solvent is one or both of anhydrous ethanol and isopropanol; and the initiator is initiator AIBN.

[0026] As a preferred technical solution of the present invention, in step 3), the heating and stirring is heating and stirring at a temperature of 60-70° C. for 4-5 hours.

[0027] As a preferred technical solution of the present invention, in step 3), the purification is to filter and then take the solid for alcohol washing; the vacuum drying is to vacuum dry at 80° C. to constant weight.

[0028] As a preferred technical solution of the present invention, in step 3), the mass ratio of the modified complex to the perillaldehyde solution is 20-21:8-10; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5-6:40-50.

[0029] The invention discloses a method for preparing a self-cleaning UV coating, which comprises the following steps:

[0030] The aqueous polyurethane acrylate emulsion, reactive monomer, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a rotation speed of 1200-1500 r / min for 50-60 minutes to obtain the product.

[0031] Beneficial effects of the present invention:

[0032] 1. After the coating of the present invention is cured, a microscopic concave-convex structure similar to a lotus leaf is formed on the surface. The nano-scale coating suspends dust, increases the water contact angle, promotes water droplets to roll off and adsorb dust, and increases the difficulty of dirt adhesion. The coating forms a surface layer rich in hydrophobic substances through self-stratification, giving the coating excellent hydrophobic and oil-resistant properties, ensuring that pollutants are removed by natural factors. The coating has the characteristics of hydrophilic and hydrophobic substances, and realizes easy cleaning and self-cleaning functions.

[0033] 2. The antibacterial particles prepared by the present invention are composed of zinc oxide wrapped by an organic polymer, which improves the dispersibility and compatibility of zinc oxide in the coating system. The wrapped zinc oxide contains multiple groups and can be used as a compatibilizer at the interface between white carbon black and the coating system, thereby improving the antibacterial and mechanical properties of the coating. DETAILED DESCRIPTION

[0034] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0035] Example 1

[0036] A self-cleaning UV coating comprises the following components by weight: 52 parts of waterborne polyurethane acrylate emulsion, 5 parts of reactive monomer, 10 parts of antibacterial particles, 2 parts of photoinitiator, 0.2 parts of defoamer, 0.2 parts of dispersant, 1 part of leveling agent, 4 parts of white carbon black, 2 parts of cosolvent and 24 parts of deionized water;

[0037] The reaction monomer is prepared by mixing methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3:2; the photoinitiator is photoinitiator 184; the defoamer is BYK019; the dispersant is BYK190; the leveling agent is BYK-3455; and the cosolvent is propylene glycol butyl ether;

[0038] The preparation of the antibacterial particles comprises the following steps:

[0039] 1) placing zinc oxide in an ethanol solution, ultrasonicating at a frequency of 200 W for 20 minutes, adding a silane coupling agent NQ62, stirring and mixing at a temperature of 50° C. for 3 hours, cooling to room temperature, centrifuging to obtain a solid, washing it three times with anhydrous ethanol, placing it in an oven and vacuum drying it at a temperature of 80° C. for 6 hours to obtain prefabricated particles; the mass ratio of the zinc oxide, the ethanol solution and the silane coupling agent NQ62 is 20:60:8;

[0040] 2) In an inert nitrogen atmosphere, the prefabricated particles and anhydrous ethanol were stirred and mixed at a speed of 500 r / min for 15 minutes, eugenol, oleic acid and glycidyl methacrylate were added and stirred at a speed of 1000 r / min for 30 minutes, and then the initiator AIBN was added and stirred at 60°C for 5 hours. After cooling to room temperature, centrifugation was performed, and the mixture was washed three times with anhydrous ethanol. After being placed in an oven and vacuum dried at 70°C for 8 hours, a modified composite was obtained; the mass ratio of the prefabricated particles, anhydrous ethanol, eugenol, oleic acid, glycidyl methacrylate and initiator AIBN was 20:60:11:2.2:16:0.8;

[0041] 3) The modified complex is immersed in a perillaldehyde solution, heated and stirred at 60°C for 4 hours, filtered, and then the solid is washed with alcohol three times, placed in an oven at 80°C and vacuum dried to constant weight to obtain antibacterial particles; the mass ratio of the modified complex to the perillaldehyde solution is 20:8; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5:40.

[0042] The preparation method of the self-cleaning UV coating comprises the following steps:

[0043] The aqueous polyurethane acrylate emulsion, reactive monomers, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a speed of 1200 r / min for 50 minutes to obtain the product.

[0044] Example 2

[0045] A self-cleaning UV coating comprises the following components by weight: 56 parts of waterborne polyurethane acrylate emulsion, 5.8 parts of reactive monomer, 11 parts of antibacterial particles, 2.2 parts of photoinitiator, 0.25 parts of defoamer, 0.22 parts of dispersant, 1.2 parts of leveling agent, 4.5 parts of white carbon black, 2.5 parts of cosolvent and 26 parts of deionized water;

[0046] The reaction monomer is a mixture of methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3.2:3; the photoinitiator is photoinitiator 184; the defoamer is BYK019; the dispersant is BYK190; the leveling agent is BYK-3455; and the cosolvent is propylene glycol butyl ether;

[0047] The preparation of the antibacterial particles comprises the following steps:

[0048] 1) placing zinc oxide in an ethanol solution, ultrasonically treating at a frequency of 225 W for 22 minutes, adding a silane coupling agent NQ62, stirring and mixing at a temperature of 52° C. for 3.2 hours, cooling to room temperature, centrifuging to obtain a solid, washing three times with anhydrous ethanol, placing in an oven and vacuum drying at a temperature of 82° C. for 6.5 hours to obtain prefabricated particles; the mass ratio of the zinc oxide, the ethanol solution and the silane coupling agent NQ62 is 22:62:8.5;

[0049] 2) In an inert nitrogen atmosphere, the prefabricated particles and anhydrous ethanol were stirred and mixed at a speed of 575 r / min for 16 minutes, eugenol, oleic acid and glycidyl methacrylate were added and stirred at a speed of 1050 r / min for 32 minutes, and then the initiator AIBN was added and stirred at 62° C. for 5.2 hours. After cooling to room temperature, the mixture was centrifuged, washed three times with anhydrous ethanol, and placed in an oven at 72° C. for vacuum drying for 8.5 hours to obtain a modified composite. The mass ratio of the prefabricated particles, anhydrous ethanol, eugenol, oleic acid, glycidyl methacrylate and initiator AIBN was 22:62:11.2:2.3:16.5:0.85.

[0050] 3) The modified complex is immersed in a perillaldehyde solution, heated and stirred at 62°C for 4.2 hours, filtered, and the solid is washed with alcohol three times. The solid is placed in an oven and vacuum dried at 80°C to constant weight to obtain antibacterial particles. The mass ratio of the modified complex to the perillaldehyde solution is 20.2:8.5. The perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5.2:42.

[0051] The preparation method of the self-cleaning UV coating comprises the following steps:

[0052] The aqueous polyurethane acrylate emulsion, reactive monomers, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a rotation speed of 1275 r / min for 52 minutes to obtain the product.

[0053] Example 3

[0054] A self-cleaning UV coating comprises the following components by weight: 60 parts of waterborne polyurethane acrylate emulsion, 6.5 parts of reactive monomer, 11.5 parts of antibacterial particles, 2.5 parts of photoinitiator, 0.3 parts of defoamer, 0.25 parts of dispersant, 1.5 parts of leveling agent, 5 parts of white carbon black, 3 parts of cosolvent and 27 parts of deionized water;

[0055] The reaction monomer is a mixture of methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3.5:3.5; the photoinitiator is photoinitiator 184; the defoamer is BYK019; the dispersant is BYK190; the leveling agent is BYK-3455; and the cosolvent is propylene glycol butyl ether;

[0056] The preparation of the antibacterial particles comprises the following steps:

[0057] 1) placing zinc oxide in an ethanol solution, ultrasonically treating at a frequency of 250 W for 25 minutes, adding a silane coupling agent NQ62, stirring and mixing at a temperature of 55° C. for 3.5 hours, cooling to room temperature, centrifuging to obtain a solid, washing it three times with anhydrous ethanol, placing it in an oven and vacuum drying it at a temperature of 85° C. for 7 hours to obtain prefabricated particles; the mass ratio of the zinc oxide, the ethanol solution and the silane coupling agent NQ62 is 23:65:9;

[0058] 2) In an inert nitrogen atmosphere, the prefabricated particles and anhydrous ethanol were stirred and mixed at a speed of 650 r / min for 18 minutes, eugenol, oleic acid and glycidyl methacrylate were added and stirred at a speed of 1100 r / min for 35 minutes, and then the initiator AIBN was added and stirred at 65°C for 5.5 hours. After cooling to room temperature, the mixture was centrifuged, washed with anhydrous ethanol three times, and placed in an oven at 75°C for vacuum drying for 9 hours to obtain a modified composite; the mass ratio of the prefabricated particles, anhydrous ethanol, eugenol, oleic acid, glycidyl methacrylate and initiator AIBN was 25:65:11.5:2.4:17:0.9;

[0059] 3) The modified complex is immersed in a perillaldehyde solution, heated at 65°C and stirred for 4.5 hours, then filtered, the solid is washed with alcohol three times, placed in an oven at 80°C and vacuum dried to constant weight to obtain antibacterial particles; the mass ratio of the modified complex to the perillaldehyde solution is 20.5:9; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5.5:45.

[0060] The preparation method of the self-cleaning UV coating comprises the following steps:

[0061] The aqueous polyurethane acrylate emulsion, reactive monomers, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a rotation speed of 1350 r / min for 55 minutes to obtain the product.

[0062] Example 4

[0063] A self-cleaning UV coating comprises the following components by weight: 64 parts of waterborne polyurethane acrylate emulsion, 7 parts of reactive monomer, 12.2 parts of antibacterial particles, 2.8 parts of photoinitiator, 0.35 parts of defoamer, 0.28 parts of dispersant, 1.8 parts of leveling agent, 5.5 parts of white carbon black, 3.5 parts of cosolvent and 28 parts of deionized water;

[0064] The reaction monomer is a mixture of methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3.8:4.2; the photoinitiator is photoinitiator 184; the defoamer is BYK019; the dispersant is BYK190; the leveling agent is BYK-3455; and the cosolvent is propylene glycol butyl ether;

[0065] The preparation of the antibacterial particles comprises the following steps:

[0066] 1) placing zinc oxide in an ethanol solution, ultrasonically treating at a frequency of 275 W for 28 minutes, adding a silane coupling agent NQ62, stirring and mixing at a temperature of 58° C. for 3.8 hours, cooling to room temperature, centrifuging to obtain a solid, washing it three times with anhydrous ethanol, placing it in an oven and vacuum drying it at a temperature of 88° C. for 7.5 hours to obtain prefabricated particles; the mass ratio of the zinc oxide, the ethanol solution and the silane coupling agent NQ62 is 24:68:9.5;

[0067] 2) In an inert atmosphere of nitrogen, the prefabricated particles and anhydrous ethanol were stirred and mixed at a speed of 725 r / min for 19 minutes, eugenol, oleic acid and glycidyl methacrylate were added and stirred at a speed of 1150 r / min for 38 minutes, and then the initiator AIBN was added and stirred at 68°C for 5.8 hours. After cooling to room temperature, the mixture was centrifuged, washed three times with anhydrous ethanol, and placed in an oven at 78°C for vacuum drying for 9.5 hours to obtain a modified composite; the mass ratio of the prefabricated particles, anhydrous ethanol, eugenol, oleic acid, glycidyl methacrylate and initiator AIBN was 28:68:11.8:2.5:17.5:0.95;

[0068] 3) The modified complex is immersed in a perillaldehyde solution, heated and stirred at 68°C for 4.8 hours, filtered, and the solid is washed with alcohol three times, placed in an oven and vacuum dried at 80°C to constant weight to obtain antibacterial particles; the mass ratio of the modified complex and the perillaldehyde solution is 20.8:9.5; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5.8:48.

[0069] The preparation method of the self-cleaning UV coating comprises the following steps:

[0070] The aqueous polyurethane acrylate emulsion, reactive monomers, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a rotation speed of 1425 r / min for 58 minutes to obtain the product.

[0071] Example 5

[0072] A self-cleaning UV coating comprises the following components by weight: 68 parts of waterborne polyurethane acrylate emulsion, 8 parts of reactive monomer, 13 parts of antibacterial particles, 3 parts of photoinitiator, 0.4 parts of defoamer, 0.3 parts of dispersant, 2 parts of leveling agent, 6 parts of white carbon black, 4 parts of cosolvent and 30 parts of deionized water;

[0073] The reaction monomer is a mixture of methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 4:5; the photoinitiator is photoinitiator 184; the defoamer is BYK019; the dispersant is BYK190; the leveling agent is BYK-3455; and the cosolvent is propylene glycol butyl ether;

[0074] The preparation of the antibacterial particles comprises the following steps:

[0075] 1) placing zinc oxide in an ethanol solution, ultrasonicating at a frequency of 300 W for 30 minutes, adding a silane coupling agent NQ62, stirring and mixing at a temperature of 60° C. for 4 hours, cooling to room temperature, centrifuging to obtain a solid, washing it three times with anhydrous ethanol, placing it in an oven at a temperature of 90° C. and vacuum drying it for 8 hours to obtain prefabricated particles; the mass ratio of the zinc oxide, the ethanol solution and the silane coupling agent NQ62 is 26:70:10;

[0076] 2) In an inert atmosphere of nitrogen, the prefabricated particles and anhydrous ethanol were stirred and mixed at a speed of 800 r / min for 20 minutes, eugenol, oleic acid and glycidyl methacrylate were added and stirred at a speed of 1200 r / min for 40 minutes, and then the initiator AIBN was added and stirred at 70°C for 6 hours. After cooling to room temperature, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried in an oven at 80°C for 10 hours under vacuum to obtain a modified composite. The mass ratio of the prefabricated particles, anhydrous ethanol, eugenol, oleic acid, glycidyl methacrylate and initiator AIBN was 30:70:12:2.6:18:1.0.

[0077] 3) The modified complex is immersed in a perillaldehyde solution, heated at 70°C and stirred for 5 hours, then filtered, the solid is washed with alcohol three times, placed in an oven at 80°C and vacuum dried to constant weight to obtain antibacterial particles; the mass ratio of the modified complex to the perillaldehyde solution is 21:10; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 6:50.

[0078] The preparation method of the self-cleaning UV coating comprises the following steps:

[0079] The aqueous polyurethane acrylate emulsion, reactive monomers, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a speed of 1500 r / min for 60 minutes to obtain the product.

[0080] Comparative Example 1

[0081] Compared with Example 3, the difference in Comparative Example 1 is that no silane coupling agent is used in step 1), and the other components, preparation steps and parameters are the same.

[0082] Comparative Example 2

[0083] Compared with Example 3, the difference in Comparative Example 2 is that eugenol is not used in step 2), and the other components, preparation steps and parameters are the same.

[0084] Comparative Example 3

[0085] Compared with Example 3, the difference in Comparative Example 3 is that oleic acid is not used in step 2), and the other components, preparation steps and parameters are the same.

[0086] Comparative Example 4

[0087] Compared with Example 3, Comparative Example 4 is different in that glycidyl methacrylate is not used in step 2), and the other components, preparation steps and parameters are the same.

[0088] Comparative Example 5

[0089] Compared with Example 3, the difference in Comparative Example 5 is that perillaldehyde is not used in step 3), and the other components, preparation steps and parameters are the same.

[0090] After the coatings prepared in Examples 1-5 and Comparative Examples 1-5 were cured at 365 nm UV, the following performance tests were performed respectively.

[0091] Mechanical properties test: tensile strength and elongation at break were tested according to GB / T16777-2008, and the test results are shown in Table 1;

[0092] Antibacterial performance test: According to GB / T 21866-2008, the test results are shown in Table 2.

[0093] Table 1

[0094] Tensile strength(MPa) Elongation at break (%) Example 1 16.2 246 Example 2 16.6 257 Example 3 16.8 261 Example 4 16.3 249 Example 5 16.4 253 Comparative Example 1 12.4 161 Comparative Example 2 13.1 179 Comparative Example 3 14.2 192 Comparative Example 4 14.7 201 Comparative Example 5 14.3 194

[0095] It can be seen from the test results in Table 1 that, compared with Comparative Examples 1-5, the UV coatings prepared in Examples 1-5 have better tensile strength and elongation at break after curing.

[0096] Table 2

[0097]

[0098]

[0099] From the test results in Table 2, it can be seen that compared with Comparative Examples 1-5, the UV coatings prepared in Examples 1-5 have significant antibacterial properties after curing.

[0100] From the examples and comparative examples, combined with the analysis of Table 1 and Table 2, it can be seen that this is because the antibacterial particles prepared by the present invention are composed of zinc oxide wrapped by an organic polymer, wherein zinc oxide serves as a core particle and its surface is covered by a layer of polymer. This structure not only improves the dispersibility and compatibility of zinc oxide in the coating system, but also forms a chemical bond connection through the grafting reaction of the epoxy group with the carboxyl group in the coating system and the hydroxyl group on the surface of the white carbon black. In addition, the zinc oxide wrapped by the organic polymer contains a non-polar benzene ring structure, a polar epoxy group and a hydroxyl group, which can be used as a compatibilizer at the interface between the white carbon black and the coating system, significantly enhancing the dispersibility and compatibility of the white carbon black in the system.

[0101] In addition, the present invention can improve the tensile strength of the coating by adding the epoxy group of glycidyl methacrylate, and oleic acid is added to the coating system as a plasticizer and chain extender to enhance the toughening effect, which can effectively improve its elongation at break; in addition, the long side chain of oleic acid is conducive to the sliding between molecular chains, which can drive the contact between white carbon black and other components of the coating system to form more cross-linked network structures, densify the network structure, and significantly increase its mechanical properties. The amino group on the silane coupling agent can form an imine bond with perillaldehyde, and the double bond group introduced by it participates in the curing and cross-linking reaction of the coating system, and can introduce organic antibacterial components into the coating, making the coating more antibacterial, while increasing the binding force between the antibacterial particles and the coating system, effectively improving its mechanical properties.

[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A self-cleaning UV coating, characterized in that: The components include the following by weight: 52-68 parts of waterborne polyurethane acrylate emulsion, 5-8 parts of reactive monomer, 10-13 parts of antibacterial particles, 2-3 parts of photoinitiator, 0.2-0.4 parts of defoamer, 0.2-0.3 parts of dispersant, 1-2 parts of leveling agent, 4-6 parts of white carbon black, 2-4 parts of cosolvent and 24-30 parts of deionized water; Wherein, the antibacterial particles are modified nano zinc oxide, and the preparation comprises the following steps: 1) placing zinc oxide in an ethanol solution and mixing it by ultrasonication, adding a silane coupling agent, heating and stirring the mixture, cooling to room temperature, centrifuging and washing the solid, placing it in an oven and vacuum drying it to obtain prefabricated particles; 2) in an inert atmosphere, mechanically stirring and mixing the prefabricated particles and the organic solvent, adding eugenol, oleic acid and glycidyl methacrylate and stirring at high speed, adding an initiator and heating and stirring, cooling to room temperature, centrifuging, washing, placing in an oven and vacuum drying to obtain a modified composite; 3) immersing the modified complex in a perillaldehyde solution, heating and stirring, and then purifying it, placing it in an oven and vacuum drying it to obtain antibacterial particles; Wherein, in step 1), the mass ratio of zinc oxide, ethanol solution and silane coupling agent is 20-26:60-70:8-10; and the silane coupling agent is silane coupling agent NQ62.

2. A self-cleaning UV coating according to claim 1, characterized in that: The reaction monomer is prepared by mixing methacrylic acid and ethoxylated pentaerythritol tetraacrylate in a mass ratio of 3-4:2-5.

3. A self-cleaning UV coating according to claim 1, characterized in that: The leveling agent is a polyether siloxane copolymer leveling agent; the cosolvent is one or two of ethylene glycol butyl ether, propylene glycol butyl ether and propylene glycol methyl ether.

4. A self-cleaning UV coating according to claim 1, characterized in that: In step 1), the ultrasonic mixing is performed at a frequency of 200-300W for 20-30 minutes; the heating stirring mixing is performed at a temperature of 50-60°C for 3-4 hours; the washing is performed three times with anhydrous ethanol; and the vacuum drying is performed at a temperature of 80-90°C for 6-8 hours.

5. The self-cleaning UV coating according to claim 1, characterized in that: In step 2), the inert atmosphere is a nitrogen inert atmosphere; the mechanical stirring and mixing is stirring and mixing at a speed of 500-800 r / min for 15-20 min; the high-speed stirring is high-speed stirring at a speed of 1000-1200 r / min for 30-40 min; the heated stirring is stirring at a temperature of 60-70°C for 5-6 h; the washing is washing three times with anhydrous ethanol; and the vacuum drying is vacuum drying at a temperature of 70-80°C for 8-10 h.

6. The self-cleaning UV coating according to claim 1, characterized in that: In step 2), the mass ratio of the prefabricated particles, the organic solvent, eugenol, oleic acid, glycidyl methacrylate and the initiator is 20-30:60-70:11-12:2.2-2.6:16-18:0.8-1.0; the organic solvent is one or two of anhydrous ethanol and isopropanol; and the initiator is initiator AIBN.

7. The self-cleaning UV coating according to claim 1, characterized in that: In step 3), the heating and stirring is heating and stirring at 60-70° C. for 4-5 hours; the purification is filtering and then washing the solid with alcohol; and the vacuum drying is vacuum drying at 80° C. to constant weight.

8. The self-cleaning UV coating according to claim 1, characterized in that: In step 3), the mass ratio of the modified complex to the perillaldehyde solution is 20-21:8-10; the perillaldehyde solution is prepared by mixing perillaldehyde and ethanol in a mass ratio of 5-6:40-50.

9. A method for preparing a self-cleaning UV coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The aqueous polyurethane acrylate emulsion, reactive monomer, antibacterial particles, photoinitiator, defoamer, leveling agent, dispersant, white carbon black, co-solvent and deionized water are mixed at a rotation speed of 1200-1500 r / min for 50-60 minutes to obtain the product.

Citation Information

Patent Citations

  • Self-cleaning aqueous UV cured paint and preparation method thereof

    CN105419625A

  • Water-based UV anti-bacterial coating and preparing method thereof

    CN105949989A